The Bar-On Model and Multifactor Measure of Human Performance: Validation and Application - Bar-On, Reuven; Fiedeldey-Van Dijk, Carina (Frontiers in Psychology, 2022)
In this article, we describe the ongoing validation and application of the Bar-On model of human performance that is assessed with the Multifactor Measure of Performance (MMP) . The MMP is a psychometric instrument designed to study, evaluate and enhance performance. We discuss the meaning and importance of performance, and explain the need for creating and applying a comprehensive model and measure of this construct. To address this need, the MMP is structurally organized to assess and strengthen 18 Core Factors that contribute to performance. Five Ring Factors were added to facilitate a deeper understanding of leadership, industriousness, productiveness, risk for burnout, and coachability. Together, they represent a multifactor approach that focuses on current behavior of the “whole person” by evaluating physical, cognitive, personal, social, and inspirational factors combined. We discuss the properties of the MMP’s normative population, as the baseline for accurate reporting, tailored to different workplace activities and needs. We conclude with recommendations for researchers and practitioners to apply this model and measure. Possible limitations of the research conducted are also discussed, together with the need for additional studies to address them.